Providers' perspectives of barriers and facilitators to scale-up of mental health care in the public health delivery system of Mozambique: a qualitative inquiry - Jennifer J. Mootz; Lindsey de Vos; Melissa Stockton; Annika C. Sweetland; Bianca Kann; Chariz Seijo; Charl Bezuidenhout; Antonio Suleman; Paulino Feliciano; Palmira F. dos Santos; Rachel Shelton; Lawrence A. Palinkas; et al. (BMC, 2024)
Abstract Background A central challenge to closing the mental health treatment gap in low- and middle-income countries (LMICs) is determining the most effective pathway for delivering evidence-based mental health services. We are conducting a cluster-randomized, Type 2 hybrid implementation-effectiveness trial across 20 districts of Mozambique called the Partnerships in Research to Implement and Disseminate Sustainable and Scalable EBPs (PRIDE) program. Following training of nonspecialized providers in facilitation of evidence-based treatments for mental health and informed by the Consolidated Framework for Implementation Research (CFIR), we identified how PRIDE compares to care as usual and the perceived barriers and facilitators of implementation and modifications needed for widescale service delivery and scale-up. Methods We conducted rapid ethnographic assessment using freelisting among 34 providers, followed by four focus group discussions (n = 29 participants) with a subsample of psychiatric technicians and primary care providers from 14 districts in Nampula Province. We used Thematic Analysis to inductively apply open codes to transcripts and then deductively applied the CFIR domains and constructs to organize open codes. Results The main Outer Setting constructs relevant to implementation were recognition that patient mental health needs were significant. Additionally, numerous community-level characteristics were identified as barriers, including distance between clinics; shortage of providers; and low awareness of mental health problems, stigma, and discrimination among community members towards those with mental health struggles. The PRIDE program was perceived to offer a relative advantage over usual care because of its use of task-sharing and treating mental illness in the community. PRIDE addressed Inner Setting barriers of having available resources and training and provider low self-efficacy and limited knowledge of mental illness. Providers recommended leadership engagement to give support for supervision of other task-shared professionals delivering mental healthcare. Conclusions Primary care providers and psychiatric technicians in Mozambique perceived the relative advantage of the PRIDE program to address mental health treatment access barriers and offered recommendations for successful sustainment and scale up of integrated mental health care.